Το περιοδικό missionary herald: Μια αθησαύριστη πηγή για την ιστορία του Μικρασιατικού ελληνισμού - Κισκήρα, Κωνσταντίνα (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1995)
The ABCFM (American Board of Commisioners for Foreign Missions) was organized at Bradford, Massachusetts, 1810 by a little band of men dedicating themselves to be missionaries to the heathen. Most of these men were students of secret religious societies at Andover Theological Seminary, by that time, Andover Theological Seminary was re-invigorating New England Congregationalism. Thus, with a comparative cosmopolitan outlook, the American Board (now United Church Board for World Ministries) in the early nineteenth century was taking missions around the world. The attention of American Christians was first turned to the Ottoman Empire as a field for missionary effort, when PI. Fisk and L. Parsons were selected to begin a mission to Palestine 1819. It soon became evident that there was no hope of reaching the Jews and the Moslems in Palestine, so the first thing to be done was to attempt to reform the Oriental Churches. Thus the ABCFM led the foundations of the Syrian Mission (1823), the Armenian Mission (1830-1831), the Mission to Greece (1831) and the Nestorian Mission (1834). Mission stations, schools, medical work and publications were initiated among the Bulgarians in 1858 and educational work was began among the Albanians in 1889. Driven by a compelling sense of Christian duty among hostility isolation and deprivation, the American Board Missionaries persisted in founding schools, mission presses and hospitals in the Ottoman Empire for over a century. The organ of the American Board was its monthly publication, the Missionary Herald ( 1820-1832). Information about the Ottoman Empire covers approximately 25-30% of the material in each issue. Data concerning Greece is limited to the years 1831-1869, while information about the Greeks living under Turkish occupation is dispersed